Implementation of Lean Manufacturing Methodology and Its Application: A Literature Review - Manurung, Martin; Anizar, Anizar; Ishak, Aulia (Jurnal Sistem Teknik Industri, 2024)
This study aims to investigate and analyze several previous works of relevant literature on the Lean Manufacturing technique in international journals. The methodology used to review the previous studies was carried out through a survey based on descriptive, qualitative, and bibliographical surveys in International Journal with restriction to the period of publication from 2017 – 2022 published on databases and electronic journals in English with the scope to examine and analyze in-depth the extent to which literature used to discuss results in the selected papers of applying the Lean Manufacturing technique in several case studies. After conducting a survey, only thirty-three articles were found with the theme of the application of Lean Manufacturing and its technique in manufacturing companies. Twenty-one techniques/tools of Lean Manufacturing were found problem-solving for waste time elimination, reducing process cycle times, and implementing process improvement. It is concluded that the most used methodology in waste reduction is Value Stream Mapping.